Adaptation of West Java Tuna Supply Chain in the Covid-19 Pandemic Era - Atikah Nurhayati; A. H. Purnomo (Faculty of Fisheries and Marine Science, Brawijaya University, 2021)
In response to the Covid -19 pandemic imposed by the Indonesian government has impacted supply chains of various important commodities, including fish products. Lockdowns and mobility restrictions forced market players to limit their activities, change strategies or even close their businesses. This research, conducted in June 2020 - February 2021 in West Java Province, aimed to analyze patterns of adaptation taken by business players of the fisheries industry in facing the pandemic. The research methodological approach was the Supply Chain Operations Reference (SCOR) framework, which relied on data collected from 80 respondents proportionally representing impacted groups of fisheries business players in the West Java Province. The results showed that fisheries business players and the government had exercised some supply chain innovative adaptations, some of which can be considered potential adaptation strategies that will improve resilience and ensure the industry’s sustainability when similar pandemic crises occur in the future. These are (i) ensuring access to domestic and international supply chains, (ii) connecting fishery production centers with processors to reduce damage to fresh fish, (iii) creating added value using optimizing existing temporary fish storages, and (iv) promoting and delivering products through digital platform or e-commerce. Keywords: